Master track of POLARSTERN cruise ANT-VIII/1 in 1 sec resolution (zipped, 133 MB), Version 2, 2025-02-07 - Hans Werner Schenke (PANGAEA, 2025)
Raw data acquired by position sensors on board RV Polarstern during expedition ANT-VIII/1 was processed to receive a validated master track which can be used as reference of further expedition data. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.